Communication: a central focus in mathematics class (2010)
Communication has been considered a fundamental aspect for knowledge of things and relationship with people, from here we can deduce its importance in learning and teaching processes. This article develops aspects related to learning and teaching in the mathematics’ classroom, focusing on communication, understood as a process of social interaction that favors negotiation of meaning, consensus, dialogue and debate. By means of the previous actions, essential processes for the development of mathematical thought can be reached, such as conjecturation and argumentation. We also analyze different strategies that transform the classroom into a vital atmosphere of interaction, where subjects acquire meaning in their interaction with the group culture, these strategies are based on the use of spaces for group work, debate and confrontation of interpretations, narratives and permanent questions by the teacher.